Os elétrons livres não são tão livres assim: uma proposta de sequência didática para o estudo da corrente elétrica - Oliveira, Samuell Antonio Amaral de (2022)
In the teaching of Physics, we, teachers, always look for alternatives so that our student is participatory and engaged in classes. We have as a goal to develop activities skills that encourage critical sense, thinking skills, and the ability to see the world from a physical perspective. The experimental activities have much to contribute to the search for teaching and learning closer to the reality of our students. How to meet this objective in remote teaching? At the unfeasibility of a physical experiment in the classroom, several software programs are used that simulate physical phenomena. Among the most used, we can mention the PhET (Physical Education Technology). As much as these software programs create a favorable condition for physics teaching, taking into consideration their character as virtual labs, we believe that students need to manipulate a real experiment, with real components. In this context, the present text reports the development of a Remote Laboratory for the experimental activities of electrical circuits, the RLab, which presents as a differential its low cost. The laboratories remotely controlled are present all over the world, as indicated in the literature. Additionally, its potential in the teaching and learning of our students is still a matter of investigation. As a central point to our investigation, we seek to raise evidence that points to RLab’s potentialities in Physics Teaching. Our research audience has 10 students, being five students from the 9th year of Elementary School and five students from the second year of High School. Our Didactic Sequence has a total of eigth classes, which aim to create conditions so that students can manipulate and carry out the investigative tests, through an experimental script. The challenge of analyzing the students’ arguments in the elaboration of the electric current model, through the CcnER Argument Analysis tool. Nevertheless, we realized that the Remote Laboratory has much to contribute to the construction of meaningful discussions, between teacher-student, through mediated classes, having a script investigation that guides and instigates the student.